INTEGRASI BAHAN AJAR BERBASIS KEARIFAN LOKAL KABUPATEN ASAHAN DALAM MENGAJAR KETERAMPILAN MEMBACA - Supiatman, Lis; Aryni, Yen; Cantika, Aisyah; Nasution, Ravli Akbar; Hardiyanti, Juni (Smart Education, 2025)
Abstract: This socialization was provided for students as prospective teachers in overcoming students' lack of interest in reading. According to the results of Rapor Pendidikan Indonesia in 2023, especially the main indicator of students' literacy skills, which this year was 49.26%, decreased by 4.59 from 2021 (53.85%) (Ministry of Education, Culture, 2023). It also happenned in Indonesia in 2022 (UNESCO). Indonesia was still ranked 60th out of 70 countries. This shows that the literacy skills of Indonesian students are getting lower (Ramadhan, 2023). Of course, it is not much different in Asahan Regency. Based on the results of monitoring and evaluation of the Integrated School Field Introduction (PLPT) course activities in several schools in Asahan Regency in 2024, students' interest in reading texts was very low, which had an impact on their learning outcomes, especially in understanding reading. One of the causes is the teaching materials that are not interesting. Therefore, the integration of local wisdom into teaching materials needs to be done so that they become more interested and motivated. The integration in question was socialized to students as prospective teachers because the knowledge they gained will be conveyed and applied to their students later (Rosyada et al., 2022). Keywords: integration, reading literacy, reading interest, local wisdom Abstrak: Kegiatan ini bertujuan untuk memberi pembekalan kepada mahasiswa sebagai calon guru dalam mengatasi kurang minatnya siswa untuk membaca. Menurut hasil Rapor Pendidikan Indonesia tahun 2023 terutama indikator utama kemampuan literasi siswa yang tahun ini 49,26% mengalami penurunan 4,59 dari 2021 (53,85%) (Kementerian Pendidikan, Kebudayaan, 2023). Sama halnya dengan kemampuan literasi siswa Indonesia tahun 2022 (UNESCO). Indonesia masih berada pada peringkat ke-60 dari 70 negara. Ini menunjukan bahwa kemampuan literasi siswa Indonesia semakin rendah (Ramadhan, 2023). Tentu tidak jauh berbeda di Kabupaten Asahan. Berdasarkan hasil monitoring dan evaluasi pada kegiatan mata kuliah Pengenalan Lapangan Persekolahan Terpadu (PLPT) di beberapa sekolah di Kabupaten Asahan tahun 2024, minat siswa untuk membaca teks sangatlah rendah sehingga berdampak terhadap hasil belajar mereka terutama dalam memahami bacaan. Salah satu penyebabnya adalah bahan ajar yang kurang menarik. Oleh karena itu, pengintegrasian kearifan lokal ke dalam bahan ajar perlu dilakukan supaya mereka menjadi lebih tertarik dan termotivasi. Pengintegrasian yang dimaksud disosialisasikan kepada mahasiswa sebagai calon guru karena pengetahuan yang mereka peroleh akan disampaikan dan diterapkan kepada siswa mereka nanti (Rosyada et al., 2022).Kata kunci: integrasi, kearifan lokal, literasi membaca, minat membaca